Osthole sensitizes with radiotherapy to suppress tumorigenesis of human nasopharyngeal carcinoma in vitro and in vivo - Peng, Lin (Cancer Manag Res, 2018)
BACKGROUND: Radiotherapy is one of the most comment and useful treatment for nasopharyngeal carcinoma (NPC), but the radioresistance remains a major obstacle. Osthole, a natural coumarin derivative, has been shown to have anti-tumor and anti-inflammatory activity. However, the relationship between osthole and NPC treatment, especially for radiotherapy, is still elusive. METHODS: Osthole with or without X ray radiotherapy treated with CNE2 cells, a human EC cell line. Cell viability, proliferation, migration and apoptosis were measured by MTT, colony formation, Annexin V/PI double staining, Transwell assay, respectively. NPC tumor models were established on BALB/c nude mice by subcutaneously injection of CNE2 cells and the effect of osthole and radiotherapy on tumor growth in vivo was studied. RESULTS: We found that in a dose-dependent manner, osthole could individually, and synergistically with radiotherapy, reduce NPC cell (CNE2) viability, proliferation, migration, and invasion, and induce apoptosis, respectively. This effect of anti-tumor growth and induction of apoptosis was further confirmed in mice induced by subcutaneously injection with CNE2 cells and following treated with osthole or/and radiation. CONCLUSION: Osthole increases the effect of radiotherapy on anti-human nasopharyngeal cancer.